Adhesion to a new CAD/CAM resin composite: Effects of the machining roughness simulation, surface treatments, and long-term aging. (October 2022) - Machry, Renan V.; Pilecco, Rafaela O.; Valcanaia, André; Pereira, Gabriel K.R.; Bottino, Marco C.; Valandro, Luiz Felipe
Abstract: Objectives: To evaluate the effect of surface treatments, finishing condition (polished vs. ground) and aging on the microtensile bond strength of a CAD/CAM resin composite to resin cement. Materials and methods: CAD/CAM resin composite blocks (Tetric CAD HT) were sectioned (7 × 12 × 4 mm), randomly divided according to finishing condition (polished or ground) and surface treatment groups (Ctrl: no treatment; AA: air-abrasion with 110 μm Al2 O3 powder; TBS: tribochemical silica coating). A coupling agent corresponding to each surface treatment was applied for cementation (Ctrl and AA groups: ExciTE F DSC; TBS group: RelyX Ceramic Primer) and each block was adhesively cemented (Variolink N) with another one from the same conditioning. Next, 1 mm 2 cross-section beams were produced after sectioning, with half being tested under microtensile test after 24 h, while the other half was aged (25, 000 cycles of thermocycling + 90 days of storage) (n = 50). Contact angle and Scanning Electron Microscopy (SEM) analysis were performed. Bond strength data (MPa) were statistically analyzed using Three-way ANOVA and Tukey tests (α = 0.05). The failure types were examined and classified as predominantly adhesive, cohesive or mixed under stereomicroscopy. Results: The surface treatments (AA and TBS) promoted higher bond strength than the Ctrl group. Grinding finishing improved the bond strength only when no treatment was performed (Ctrl group), having a negative effect for the TBS treatment. The long-term aging damaged the resin bond, independent of the condition. The failure analysis showed that 92% of the failures were classified as adhesive in the baseline conditions, and 94.7% in aged specimens. TBS showed the lowest contact angle among the tested groups for both conditions (baseline and aged). Conclusion: Surface conditioning with alumina particle air-abrasion or tribochemical silica coating improves the bond strength. CAD/CAM milling roughness induces better surface condition for adhesion, in particular when no treatment is performed. Bond degradation occurs after long-term aging for all the test conditions. Clinical relevance: When luting CAD/CAM resin composite restorations, the surface treatment and roughness due to the grinding by burs in the manufacturing process influence the adhesion of restoration to resin cement. Highlights: The machining roughness simulation influences the bond strength of the CAD-CAM resin composite to resin cement. Alumina particle air-abrasion lead to the higher bond strength for a milled composite resin surface. Treated polished surfaces has higher reduction in bond strength after long-term aging. Tribochemical surface treatment has the lowest reduction in bond strength after aging.